2021
DOI: 10.1177/1478210320983499
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood teacher research and social-emotional learning: Implications for the development of culturally sensitive curriculum in Singapore

Abstract: Teacher research has been promoted as a context-relevant approach to improving children’s learning experiences in early childhood settings. In this article, we focus on social-emotional learning (SEL), a crucial domain of the early childhood curriculum, to illustrate the role of teacher research in changing early childhood teachers’ everyday practices. We present an informative project on facilitating toddlers’ conflict resolution to exemplify the process of early childhood teacher research for supporting SEL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“… Note. FC = formal curriculum; PC = perceived curriculum; OC = operational curriculum. a Category refers to which levels of curriculum have been involved in the research reported by a particular article. b Australia and New Zealand are also included in Yang et al’s (2022) study. c Nine other countries are also included in Oberhuemer’s (2005) study. d U.S. is also included in Wang et al’s (2008) study. e Seven other countries are also included in Miyahara and Meyers’s (2008) analysis. f Norway is also included in Hammer and He’s (2016) study. g U.S.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Note. FC = formal curriculum; PC = perceived curriculum; OC = operational curriculum. a Category refers to which levels of curriculum have been involved in the research reported by a particular article. b Australia and New Zealand are also included in Yang et al’s (2022) study. c Nine other countries are also included in Oberhuemer’s (2005) study. d U.S. is also included in Wang et al’s (2008) study. e Seven other countries are also included in Miyahara and Meyers’s (2008) analysis. f Norway is also included in Hammer and He’s (2016) study. g U.S.…”
Section: Resultsmentioning
confidence: 99%
“…And children are expected to participate in and enjoy various arts experiences (Kim & Kim, 2017). However, Yang et al (2022) identified five contextual considerations that deserve attention (pp. 10–11): (1) acknowledge the values of teacher-directed, explicit instruction; (2) recognize the necessity of the pre-academic preparation for young children in preschools to ease their transition to primary schools; (3) concretely illustrate how to enact the idea of “purposeful play” in the classroom; (4) justify how to meet the predetermined learning goals of distinct learning areas via integrated learning; and (5) identify the existing constraints in the wider educational landscape to smoothen the NEL framework's implementation in practice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations